Enhancing Firm Performance through Entrepreneurial Orientation and Organizational Capability - Maulana, Irfan Adzan; Susilowati, Christin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to analyze the influence of entrepreneurial orientation on firm performance among culinary SMEs in Malang City, with organizational capability as a mediating variable. Design/Methodology/Approach – This study employs an explanatory quantitative research design. Using a non-probability sampling method with a purposive sampling technique, 109 culinary MSME owners in Malang City were selected as respondents. The data were collected through questionnaires and analyzed using Partial Least Squares (PLS) with SmartPLS version 4.1.0.6 Findings – The results show that entrepreneurial orientation has a significant effect on firm performance. Furthermore, entrepreneurial orientation significantly influences organizational capability, organizational capability significantly affects firm performance, and organizational capability mediates the relationship between entrepreneurial orientation and firm performance. These findings indicate that strengthening entrepreneurial orientation and organizational capabilities can improve SME performance. Originality/Value This study provides empirical evidence on the mediating role of organizational capability in the relationship between entrepreneurial orientation and firm performance within the culinary SME sector. It offers a context-specific contribution by demonstrating how capability development strengthens the performance impact of entrepreneurial orientation, giving practical insights for SME strategic improvement.